A Novel lncRNA Regulates the Toll-Like Receptor Signaling Pathway and Related Immune Function by Stabilizing FOS mRNA as a Competitive Endogenous RNA - Fan, Hao; Lv, Zengpeng; Gan, Liping; Ning, Chao; Li, Zhui; Yang, Minghui; Zhang, Beibei; Song, Bochen; Li, Guang; Tang, Dazhi; Gao, Jinxin; Yan, Shaojia; et al. (Frontiers in Immunology, 2019)
Long noncoding RNAs (lncRNAs) have recently emerged as new regulatory molecules with diverse functions in regulating gene expression and significant roles in the immune response. However, the function of many unknown lncRNAs is still unclear. By studying the regulatory effect of daidzein (DA) on immunity, we identified a novel lncRNA with an immune regulatory function: lncRNA- XLOC_098131. In vivo, DA treatment upregulated the expression of lncRNA- XLOC_098131, FOS and JUN in chickens and affected the expression of activator protein 1 (AP-1) to regulate MAPK signaling, Toll-like receptor signaling, and related mRNA expression. It also enhanced macrophage activity and increased the numbers of blood neutrophils and mononuclear cells, which can improve the body's ability to respond to stress and bacterial and viral infections. Furthermore, DA treatment also reduced B lymphocyte apoptosis and promoted the differentiation of B lymphocytes into plasma cells, which in turn resulted in the production of more immunoglobulins and the promotion of antigen presentation. In vitro, using HEK293FT cells, we demonstrated that mir-548s could bind to and decrease the expression of both FOS and lncRNA- XLOC_098131. LncRNA- XLOC_098131 served as a competitive endogenous RNA to stabilize FOS by competitively binding to miR-548s and thereby reducing its inhibitory effect of FOS expression. Therefore, we concluded that the novel lncRNA XLOC_098131 acts as a key regulatory molecule that can regulate the Toll-like receptor signaling pathway and related immune function by serving as a competitive endogenous RNA to stabilize FOS mRNA expression.